Identification and characterizationof novel cellulase from thermophilic microbial consortium for potential application in enzymatic deinking - Hashimatul Fatma, Hashim (Universiti Malaysia Sarawak (UNIMAS), 2008)
hive of the best endoglucanase producers has been successfully isolated and identified based on the 'halo' formed on Luria Bertani (LB) agar media containing 1% (w/v) of carboxymethylcellulose (CMC) flooded with Congo Red solution. Molecular approach targeting the conserved region of 16S rRNA bacterial strains was used to further confirm the initial morphological and biochemical tests result. A phylogenetic tree construction using Neighbour-Joining, Maximum Parsimony and Maximum Likelihood analysis was used to further strengthen the findin he best endoglucanase producer strain in this research was found to be bacterial isolate of Bacillus licheniformis BL-P7. PCR amplification using endoglucanase primers produced a PCR product of 750 bp in molecular weight of size. In silico analysis of sequencing product indicate this gene is coding for an extracellular alkaline endo-I, 4-beta-glucanase. In this study, partial of endoglucanase gene has been successfully was cloned and characterized however no expression was obtained. Bacillus licheniformis BL-P7 was inoculated into submerged liquid fermentation media utilizing sago pith waste and rice husk. An optimal condition for endoglucanase secretion by Bacillus licheniformis BL-P7 was detennined successfully. Preliminary kinetics study on crude endoglucanase enzyme was stable in wide spectrum of pH and at high temperature. Purification of the crude enzyme extract of Bacillus licheniformis BL-P7 produced in the submerged liquid fermentation to apparent homogeneity was carried out. The isoelectric point (pI) for the purified enzyme was 5.5 with the protein weight size of 35 kDa. The purified endoglucanase was very stable in wide range of pH (up to pH 12) and temperature (up to 100 0C). The enzyme action is unaffected in the presence of various metal ions. This research has conducted the trial enzymatic deinking on mixed office paper. The results revealed that enzymatic de inking profoundly have better results compared to conventional chemical deinking. Removal of ink residues and all paper properties were enhanced in terms of brightness, air permeable, tensile and tear with 50% efficiency.